Peningkatan Kemampuan Berhitung Melalui Bermain Kartu Angka Pada Anak Kelompok B Semester I Tk Muslimat Nu Punggursugih Kecamatan Ngawen Kabupaten Blora Tahun 2015/2016 - ZULAIKAH, ZULAIKAH, Drs. Sutan Syahrir Zabda, SH,MH (2015)
This research purpose is research to improve the numeracy skills of children through the card numbers. This research is a classroom action research conducted in two cycles and each cycle outsmart conducted two meetings. The subjects of this study is children kindergarten Group B Moslem Punggursugih District of Ngawen Blora totaling 13 children as recipients of actions, researcher and teacher colleagues as giving action. The data collected in this study is data about the numeracy skills of children and data on teacher learning through activities card numbers. Both of these data were collected through observation. Data were analyzed with the child's ability to count and a comparative analysis of data on teacher learning through activities card numbers analyzed by interactive analysis. The results of the analysis showed that the average prasiklus numeracy skills the child reaches 58% means that the new child numeracy skills develop according to expectations. After the first cycle measures the average numeracy skills the child reaches 69%, which means that the developing child's numeracy skills was as expected, but already there is an increase. After the second cycle measures the average child's ability to count increased by 87% means that children develop numeracy skills very baik. Main of this study is that the card number can improve numeracy skills of children in kindergarten Group B Moslem Punggursugih District of Ngawen Blora.